On the Relevance of Game Theory in Strategic Thinking - Engelbrecht, G.N. (Scientia Militaria - South African Journal of Military Studies, 2012)
The author reviews some of the applicable literature and shows how game theory can be used to predict the outcome of a strategy, explain why a particular outcome to a strategy has occurred, investigate strategy and prescribe certain rules for the making of a strategy. He concludes that game theory can aid decision makers at all levels in formulating quality strategies. In fact, game theory should be an integral and indispensable part of the strategist's toolbox.